Design process was not more what it used to be: The brand new architecture of BDELTV in Buenos Aires, 1965-1970 - Plotquin, Silvio (2021)
The Koch Polito Mill is the latest in a series of projects in which Baudizzone, Díaz, Erbin, Lestard, Traine and Varas -BDELTV- experimented with market standard systems and novel materials in innovative ways. The case allows to verify the BDELTV agenda: relationship between form, logistics and costs; the link of the construction market and the expectations of employers and clients and their speculations regarding the contents of architecture and mass media. With buildings and surprising relational installations, inspired by specific sites, known in Argentinean room as “happenings”, modernization "took over" and the common citizen found himself immersed in an everyday creative and surprising world. BDELTV's architecture seems to have nurtured this cycle of creativity and escape, of exploration and defiance of conventions, crossing the fields of architecture and art.